Comparison of Attitudes Towards Meditation Healing Exercise between the Elderly Living with Chronic Illness in Bangkok and Surabaya - Ni Putu Wulan Purnama Sari; Jintana Artsanthia (Jurnal Ners, 2018)
Introduction: Meditation healing exercise (MHE) using the SKT technique is popular in Bangkok, Thailand, while in Surabaya, Indonesia, it is relatively new and unpopular. The attitude towards MHE depends on various internal and external factors. This study aimed to compare the attitude towards MHE between the elderly who are living with hypertension (HT) and/or diabetes mellitus (DM) in Bangkok and Surabaya.Methods: This was a comparative study involving 96 and 100 elderly individuals with HT and/or DM in the communities of Surabaya and Bangkok respectively. The sample was chosen according to the aforementioned criteria. The sample size was 196. The instrument used was a valid and reliable questionnaire. Descriptive statistics, the Levene test, and an independent sample T test were used for the data analysis.Results: The majority showed a positive attitude towards MHE; the higher Mean and lower SD was found in Bangkok (19.43 and 2.41). Out of the total, 87.5% and 96.0% elderly had good attitude towards MHE in Surabaya and Bangkok respectively. There was a significant attitude difference in relation to the aspect of preferring to practice MHE between Bangkok and Surabaya (p=0.004). Overall, there was no significant attitude difference between Bangkok and Surabaya (p=0.17).Conclusion: The elderly attitude towards MHE was mostly positive and good. The elderly in Bangkok prefer to practice MHE more than in Surabaya. There was no significant attitude difference in the elderly who are living with HT and/or DM between Bangkok and Surabaya. The implementation of MHE using the SKT technique has a high possibility of being accepted personally by the elderly in both sites.